Introducing a Market Element into the Funding Mechanism of Public Education in British Columbia: A critical policy analysis of the School Amendment Act, 2002 - Fallon, Gerald; Paquette, Jerald (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThis policy study explores origins of part 6.1 of Bill 34 (School Amendment Act, 2002) and its impacts on the institutional behaviour of two public school districts in British Columbia. Part 6.1 permits school districts to raise funds through for-profit school district business companies (SDBC). The analysis found several consequences of the policy: lack of accountability of SDBCs, increased fiscal inequity among school districts, and greater responsiveness of school districts to the needs of a globally rather than locally situated community of students.